Pengaruh Likuiditas dan Profitabilitas terhadap Pertumbuhan Laba pada Tiga Perusahaan Bank Umum Syariah yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018 – 2022 - Mar’atussolehah Mar’atussolehah; Novi Mubyarto; Muhammad Ismail (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research was conducted to see whether there was an influence of liquidity and profitability on profit growth in three islamic commercial banking companies listed on the indonesia stock exchange (BEI). The phenomenon of profit growth is the company’s ability to increase net profit compared to the previous year. Good profit growth can reflect that the company’s financial performance and financial condition are good. Profit growth can be calculated by subtracting the current period’s net profit from the previous period’s net profit and the dividing by the previous period’s net profit. There are two ratios used in this research, namely the liquidity ratio (Current Ratio, Quick Ratio) and the profitability ratio (Return On Asset).